Significance of High-Containment Biological Laboratories Performing Work During the COVID-19 Pandemic: Biosafety Level-3 and -4 Labs - Yeh, Kenneth B.; Tabynov, Kairat; Parekh, Falgunee K.; Mombo, Illich; Parker, Kyle; Tabynov, Kaissar; Bradrick, Shelton S.; Tseng, Ashley S.; Yang, Ji-Rong; Gardiner, Lolly; Olinger, Gene; Setser, Bradly (Frontiers in Bioengineering and Biotechnology, 2021)
High containment biological laboratories (HCBL) are required for work on Select Agents across the spectrum of basic, applied, and translational research. These laboratories include biosafety level (BSL)-3, BSL-4, animal BSL (ABSL)-3, BSL-3-Ag (agriculture livestock), ABSL-4 laboratories, and many are equipped with aerosol test chambers for detection and challenge studies. While SARS-CoV-2 material and samples are handled in BSL-2 and not on the Select Agent list, scenarios where the risk of high culture volumes, potential exposure to aerosols, divergent high transmissible variants, and zoonosis from laboratory animals require higher BSL-3 measures. Establishing HCBLs especially those at BSL-4 is costly and needs continual investments of resources and funding to sustain labor, equipment, infrastructure, certifications, and operational needs. There are now over 50 BSL-4 laboratories, numerous biosafety-level 3 laboratories, and countless aerosol chambers that include many housed in BSL-3 and BSL-4 laboratories worldwide. Besides technical and funding challenges, there are biosecurity and dual-use risks, and local community issues to contend with in order to sustain operations. Here, we describe case histories for distinct HCBLs: representative national centers for diagnostic and reference, nonprofit organizations, and various aerosol test chambers. Case histories describe capabilities and assess activities during COVID-19 and include capacities, gaps, successes, and summarize lessons learned for future practice.